Protocol for real-time glycolytic monitoring in mammalian cells using confocal microscopy and HYlight, a biosensor for fructose 1,6-bisphosphate - Israel Pérez-Chávez; Nicolas Baeyens; Daria Ezeriņa; Esteban N. Gurzov; Joris Messens (STAR Protocols)
Summary: Here, we present a protocol for a glycolytic stress test using HYlight, a fluorescent protein-based biosensor that specifically binds fructose 1,6-bisphosphate (FBP), a product of the rate-limiting step of glycolysis. We describe steps for HYlight delivery into cells, real-time imaging by confocal microscopy, and data analysis. Compared with other techniques, HYlight allows glycolytic activity assessment in intact cells with single-cell resolution. This protocol can be applied to studies in which glycolysis might play a role, such as cancer or diabetes research.For complete details on the use and execution of this protocol, please refer to Pérez-Chávez et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.